P5.18 CENTRAL HEMODYNAMIC’ S ARE ASSOCIATED WITH DIABETIC COMPLICATIONS IN TYPE 1 DIABETES - S. Theilade; T.W. Hansen; P. Rossing (Artery Research, 2013)
Objectives: We investigate associations between central hemodynamics and complications in type 1 diabetes. Methods: Cross-sectional study, 676 type 1 diabetes patients, mean±SD age 55±13, 375(56%) male. Central hemodynamics measured by pulse wave analyses (PWA) (SphygmoCor (Atcor Medical, Australia) as central aortic systolic pressure (CASP), central pulse pressure (CPP), central diastolic pressure (CADP) and subendocardial viability ratio (SEVR) (index of myocardial oxygen supply and demand). Standardized values of hemodynamic measures were used in adjusted analyses. Complications were presence of albuminuria (≥30mg/24-hour), cardiovascular disease (CVD), retinopathy or autonomic dysfunction (heart rate variability <11 beats/minute). Results: PWAs were available in 636 patients. Mean±SD CASP: 118±17 mmHg, CADP: 75±10 mmHg, CPP: 43±14 mmHg and SEVR: 150±32. CVD (n=120) and autonomic dysfunction (n=349) was associated with: CASP (per +1 standard deviation (SD)): odds ratios (OR)=3.6(2.0–6.5) and 4.8(2.6–8.8); CPP (per +1SD): OR=2.0(1.5–2.7) and 2.2(1.6–3.1); CADP (per -1SD): OR=2.9(1.7–5.0) and 2.9(1.7–5.1); and SEVR (per -1SD): OR=1.7(1.1–2.6) and 2.4(1.6–3.5) (adjusted for gender, diabetes duration, mean arterial pressure, heart rate, height, urinary albumin excretion rate (UAER), eGFR, HbA1c, cholesterol, antihypertensive medication and smoking). None of the hemodynamic variables were associated with albuminuria (n=335) or retinopathy (n=469) (p≥0.14). However, if analysing UAER as a continuous variable, all hemodynamic variables were independently associated with level of UAER (p≤0.001). Conclusions: In patients with type 1 diabetes, central hemodynamics are independently associated with CVD, autonomic dysfunction and level of UAER, but not with albuminuria grade or retinopathy. Future studies are needed to determine if targeting central hemodynamics improve outcome.